A Study on Human Resource Management Practices in Selected Financial Institutions in Malaysia - Ismail, Anita (1999)
Human resource management (HRM) practices are part of the system and processes that are expected to be consistent with strategy. The logic connecting HRM practices and organisational is intuitively appealing, supported by theoretical arguments from a number of disciplines. The future organisation demand is to recognise itself to become effective in responding to changing environment needs. The organisation must reorganise itself to match the changing needs of its employees. Organisation also must develop a new approach to manage human resources to be effective and better result oriented.This study extends empirical research on the organisation-level impact of HRM practices. A unique national probability sample financial institutions to evaluate the association between a variety of HRM practices dimensions and perceptual measures of organisational performance, organisational climate, and quality of work life. The HRM practices focused on the twenty-five most commonly recognised area of HRM. Some important methodological issues that merit better understanding the relationship between HRM practices and organisational performance was used. The organisation selected in this study were financial institutions around Selangor and Kuala Lumpur. A structured questionnaire was developed as an instrument in collecting data. The data collected was analysed using Statistical Package for Social Science (SPSS). Descriptive statistics such as frequencies, one way ANOVA, t-test, correlation, and multiple regression was used to analyse and conclude the relationship of HRM practices and organisational performance, organisational climate, and quality of work life. This study was to examine whether the dimensions of HRM practices have relationship with organisational performance, organisational climate, and quality of work life. This was examined by comparing three levels of employees in industrial setting represented by financial institutions in Malaysia. The results showed that subgroup analyses of employees indicated that there are no differences in the perception of HRM practices, organisational performance, and quality of work life, but there is a difference in the perception of organisational climate. The HRM practices of the financial institutions are found to have positively correlated to organisational performance and quality of work life, but negatively correlated with organisational climate. In an analysis of sector-wise comparison, it was found that no inter-group differences in their perception of HRM practices, organisational performance, organisational climate, and quality of work life between the sector. The study has shown that identification of HRM practices promises to add significantly to understanding the relationship between HRM practices on organisational performance, organisational climate, and quality of work life.